Closing Wedge Osteotomy of the Femur Fixed by 90 Plate Blade in Valgus Knee Osteoarthritis: Ostéotomie de Fermeture du Fémur Fixée par une Lame de 90 dans l'Arthrose du Genou en Valgus - Ferdinand Nyankoué Mebouinz; Alioune Badara Gueye; Mohammadou Moustapha Niane; Charles Valerie Kinkpé (HEALTH SCIENCES AND DISEASE, 2024)
ABSTRACT Introduction. The closing wedge osteotomy (CWO) of the femur is a surgical technique for the conservative treatment in valgus knee osteoarthritis. The objective was to access the clinical, radiological and functional results of the CWO of the femur fixed by a 90° blade-plate. Methodology. This was a retrospective analytical study from January 2011 to January 2020 in Dakar. It included all patients operated on for closing wedge osteotomy of the femur fixed with a 90° plate blade. The International Knee Society (IKS) score was used to assess functional outcome. Preoperative and last follow-up values of IKS scores and mechanical femorotibial angles were compared. Results. We studied 20 patients (21 knees), including 14 women and 6 men, were included. The satisfaction rate for the final functional result was 85%. It concerned the improvement of the pain and the axis of the limb. Mean IKS scores had significantly increased to 39.6; 17.2 and 56.8 points respectively for knee, function and global IKS (p<0.05). At the last follow-up, the IKS function score was good in 86% of cases. The average consolidation time was 4.3 months. The average postoperative mechanical femorotibial angle was 0° ± 2.4 with an average angular correction performed of 16.2°. The final correction was in varus from 0 to 4° in 12 cases and in valgus from 0 to 4° in 9 cases. The mean loss of correction was 2.5°. The main complications were delayed consolidation in 9 cases, rupture of the lateral hinge in 8 cases, loss of correction in 7 cases, appearance of medial compartment wear in 4 cases, 2 cases of infection and dismantling of the plate blade. Within the range of ±4°, the varus or valgus correction did not influence the functional result. Conclusion. The closing wedge osteotomy of the femur fixed by a 90° plate blade improves knee function and delays prosthetic surgery. Delayed consolidation is the most frequent complication in the postoperative evolution. RÉSUMÉ Introduction. L'ostéotomie cunéiforme fermante (OCF) du fémur est une technique chirurgicale pour le traitement conservateur de l'arthrose du genou en valgus. L'objectif était d'évaluer les résultats cliniques, radiologiques et fonctionnels de l'OCF du fémur fixée par une lame-plaque à 90°. Méthodologie. Il s'agit d'une étude analytique rétrospective de janvier 2011 à janvier 2020 au Centre Hospitalier de l'Ordre de Malte à Dakar (Sénégal). Elle a inclus tous les patients opérés d'une OCF du fémur fixée par une lame-plaque à 90°. Le score de l'International Knee Society (IKS) a été utilisé pour évaluer le résultat fonctionnel. Les valeurs préopératoires et de dernier suivi des scores IKS et des angles mécaniques fémoro-tibiaux ont été comparées. Résultats. Nous avons étudié 20 patients (21 genoux), dont 14 femmes et 6 hommes, ont été inclus. Le taux de satisfaction du résultat fonctionnel final était de 85%. Il concernait l'amélioration de la douleur et de l'axe du membre. Les scores IKS moyens avaient significativement augmenté à 39,6 ; 17,2 et 56,8 points respectivement pour le genou, la fonction et l'IKS global (p<0,05). Au dernier suivi, le score IKS fonctionnel était bon dans 86% des cas. La durée moyenne de consolidation était de 4,3 mois. L'angle fémoro-tibial mécanique postopératoire moyen était de 0° ± 2,4 avec une correction angulaire moyenne de 16,2°. La correction finale était en varus de 0 à 4° dans 12 cas et en valgus de 0 à 4° dans 9 cas. La perte moyenne de correction était de 2,5°. Les principales complications ont été un retard de consolidation dans 9 cas, une rupture de la charnière latérale dans 8 cas, une perte de correction dans 7 cas, l'apparition d'une usure du compartiment médial dans 4 cas, 2 cas d'infection et le démontage de la lame de la plaque. Dans une fourchette de ±4°, la correction en varus ou en valgus n'a pas influencé le résultat fonctionnel. Conclusion. L'ostéotomie cunéiforme de fermeture du fémur fixée par une lame plaque à 90° améliore la fonction du genou et retarde la chirurgie prothétique. Le retard de consolidation est la complication la plus fréquente dans l'évolution postopératoire.